Murli Dhar Shad: Personality and Poet - Mushtaq, Majid; Hameed Khan, Shaista (sourcecoder, 2022)
Murli Dhar Shad was the founder of Lyallpur Cotton Mill. He was a great poet and person. He initiated the poetic meetings (Mushairas) in the city of commercial activities. His contribution in Urdu literature cannot be forgotten. Famous poets of this participated in these meetings; Jigar Muradabadi, Faiz Jhunjhanvi, Bekhud Dehlvi, Ahsan Danish etc. He has great human values in his personality. This article shows some glimpsis of his personality and poetry. It will also help the scholars to know his contribution in Urdu literature.